Overall survival of relapsed and refractory multiple myeloma patients after adjusting for crossover in the MM‐003 trial for pomalidomide plus low‐dose dexamethasone. (18th November 2014) - Morgan, Gareth; Palumbo, Antonio; Dhanasiri, Sujith; Lee, Dawn; Weisel, Katja; Facon, Thierry; Delforge, Michel; Oriol, Albert; Zaki, Mohamed; Yu, Xin; Sternas, Lars; Jacques, Christian; et al.
Summary In the phase III MM‐003 trial, pomalidomide plus low‐dose dexamethasone (POM+LoDEX) improved overall survival (OS) versus high‐dose dexamethasone (HiDEX) in 455 patients with relapsed and refractory multiple myeloma (RRMM) after treatment with bortezomib and lenalidomide. Here, a two‐stage Weibull method was used to adjust for the crossover of patients in the HiDEX arm to pomalidomide‐based therapy. The adjusted difference in median OS between patients in the POM+LoDEX and HiDEX arms was 7·0 months (12·7 vs. 5·7 months, respectively). These findings provide important evidence for understanding the clinical efficacy of pomalidomide on OS benefits seen in RRMM patients.